Pengaruh Brand Awareness dan Brand Loyalty Terhadap Keputusan Pemilihan Konsumen Agen Tour & Travel - Ramdanni, Medi; Sirait, Tongam (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of Brand Awareness and Brand Loyalty on consumer decision-making in choosing international travel services at Aya Tour & Travel. This research uses a quantitative method with data collection through questionnaires distributed to 121 respondents who have experience or intention to use the service. The analysis results show that Brand Awareness has a positive and significant effect on the Decision-Making process, where consumers with high brand awareness of Aya Tour & Travel are more confident and motivated to choose the service. Brand Loyalty also has a positive and significant impact on the Decision-Making process, with consumers who are loyal to the brand more likely to make repeat selections or recommend Aya Tour & Travel to others. Simultaneously, both Brand Awareness and Brand Loyalty positively and significantly affect Decision-Making, where these two variables complement each other and contribute to influencing consumer decisions. These findings provide valuable insights for Aya Tour & Travel's management in formulating more effective marketing strategies based on brand awareness and loyalty.